Lung Cancer Survival in Sri Lanka - Alagiyawanna, Lanka; Wijesekera, Sidath; Peiris, Vimukthini; Rupasinghe, Tiromi; Chathuranga, Damitha; Balawardena, Jayantha; Gunasekera, Dehan; Jeyakumaran, Nadarajah; Skandarajah, Thurairajah; Joseph, Nuradh (South Asian Journal of Cancer, 2023)
Introduction Lung cancer is the second commonest cancer among males in Sri Lanka. Real-world survival data are scarce, and we conducted a retrospective survival analysis among patients treated for lung cancer.Methods All patients with primary lung cancer treated at three selected units during 2015–2016 were included in the study. Data on clinicopathological and treatment delivered were extracted from clinic records. Overall survival was considered the primary end-point.Results The study population comprised 349 patients. The median age was 61 years and majority of patients (74%) were males. Adenocarcinoma (56%) was the commonest histological subtype, followed by squamous cell carcinoma (26%), whereas 6% of patients had small cell lung cancer. Only 10% of patients with non-small cell lung cancer were treated with curative intent, whereas 67% presented with systemic metastases. The median overall survival was 12 months in patients treated with curative intent and there was no significant difference between radical surgery and radiotherapy. The median overall survival was 3 months in those treated palliatively. On multivariate analysis, female gender and first-line treatment with tyrosine kinase inhibitors was associated with superior survival.Conclusion More than 90% of lung cancer patients in Sri Lanka are treated with palliative intent. Further work is needed to identify patient and care pathway barriers to ensure diagnosis at an earlier stage.
Keywords: lung cancer; survival; Sri Lanka